10.5k views
0 votes
P=s+t+r for s simplfy your answer

User Priceless
by
5.0k points

1 Answer

4 votes

Answer:

s = P - t - r

Explanation:

You are solving for the variable, s. To do so, isolate the variable. Note the equal sign, what you do to one side, you do to the other.

First, subtract the variable t from both sides of the equation:

P (- t) = s + t (-t) + r

P - t = s + r

Next, isolate the variable s by subtracting r from both sides:

P - t (-r) = s + r (-r)

P - t - r = s

s = P - t - r

s = P - t - r is your answer.

~

User StfnoPad
by
5.4k points